Corrupting youth : political education, democratic culture, and political theory - Euben, J. Peter (Princeton University Press, 1997)
In Corrupting Youth, Peter Euben explores the affinities between Socratic philosophy and Athenian democratic culture as a way to think about issues of politics and education, both ancient and modern. The book moves skillfully between antiquity and the present, from ancient to contemporary political theory, and from Athenian to American democracy. It draws together important recent work by political theorists with the views of classical scholars in ways that shine new light on significant theoretical debates such as those over discourse ethics, rational choice, and political realism,